Garanti Bank SA : Combining SME Banking Excellence with a Proposition for Women Entrepreneurs in Turkey - McCartney, Andrew; Tilyayev, Ulugbek (World Bank Group, Washington, DC, 2015)
Garanti Bankasi (Garanti) is a regional pioneer in offering products and services specifically targeted towards women entrepreneurs as a specific market segment. In 2006, Garanti created a women's entrepreneur support package specifically designed to help Turkey s women entrepreneurs to establish and grow their businesses. This was followed up with the creation of Women Entrepreneur Gatherings, in 2007, which provided additional training and educational tools and new networking opportunities. And in 2013, Garanti began collaborating with Bogazici University, a top university in Turkey, to offer an intensive mini-MBA training program for women entrepreneurs. Garanti also launched Turkey s first Woman Entrepreneur of the Year award, an initiative that showcases women who have successfully grown their business, encouraging more women entrepreneurship in the country. This case study (the study ) explores how Garanti leaders decided to focus on women entrepreneurs. It also documents and analyzes the bank s efforts to build a profitable and sustainable women in business franchise, through its three-pillar approach, including financial support, client education, and the encouragement of entrepreneurship. The case study also provides insights into how Garanti tapped into, and integrated with its highly innovative, market leading Small and Medium Enterprise, or SME banking franchise to more effectively target women in business. The study concludes with an objective assessment of the results of the program to date, offering suggestions from IFC specialists on how Garanti may further scale up its women in business initiative in the next phase of development.